Ingeniería del desempeño en las organizaciones sensible, coherentes y lucidas - Bejarano Garzón, Lilian Astrid; Meza Alvarez, Joaquin Javier (Ingeniería, 1999)
Continuous improvement leads to a higher efficiency and/or productivity which means increasing the satisfaction of the customers. The measurement reward system must be set so that employees are encouraged to work in the firm ́s interests while furthering their self-interest. Taking this to its logical conclusion, the measuring reward system should be tied to strategic drivers the firm has chosen to work with and frequent feedback enough to allow necessary changes to be made within the strategic cycle times.